Resolving sea ice dynamics in the north-western Ross Sea during the last 2.6 ka: From seasonal to millennial timescales. (1st June 2020) - Tesi, T.; Belt, S.T.; Gariboldi, K.; Muschitiello, F.; Smik, L.; Finocchiaro, F.; Giglio, F.; Colizza, E.; Gazzurra, G.; Giordano, P.; Morigi, C.; Capotondi, L.; et al.
Abstract: Time-series analyses of satellite images reveal that sea ice extent in the Ross Sea has experienced significant changes over the last 40 years, likely triggered by large-scale atmospheric anomalies. However, resolving how sea ice in the Ross Sea has changed over longer timeframes has until now remained more elusive. Here we used a laminated sediment piston core (14.6 m) collected from the Edisto inlet (Western Ross Sea) to reconstruct fast ice dynamics over the last 2.6 ka. Our goal was to first understand the climate expression of selected well-defined sediment laminae and then use these characteristics for reconstructing past sea ice behaviour across the whole sedimentary sequence. We used the recently established sea ice diatom biomarker proxy IPSO25 in combination with diatom census counts and bulk analyses. Analyses performed on a suite of discrete laminae revealed statistically significant differences between dark and light laminae reflecting different depositional conditions. Based on their respective biogeochemical fingerprints, we infer that dark laminae accumulated during sea ice thaws in early summer. Under these conditions, laminae contain relatively high concentrations of IPSO25 and display an enriched δ 13 C composition for the bulk organic matter (OM). While diatom assemblages in dark laminae are relatively homogenous, as the thaw continues later in the summer, Corethron pennatum becomes the dominant diatom species, resulting in the formation of light laminae characterized by low IPSO25 concentrations. Since C. pennatum can migrate vertically through the water column to uptake nutrients and avoid competition in oligotrophic waters, its high concentration likely reflects stratified and ice-free surface waters typical of late summer. Down-core trends show that the correlation between sediment brightness and geochemical fingerprint (i.e., IPSO25 and δ 13 C) holds throughout the record. Based on the knowledge gained at lamina level, our down-core high-resolution reconstruction shows that the summer fast ice coverage changed dramatically during the late Holocene. Specifically, we conclude that the Edisto inlet experienced regular early summer opening between 2.6 ka, and ca. 0.7 ka, after which, coastal fast ice persisted during summer months and ice-free conditions became less frequent. Comparison with previous regional ice core data suggests that the sudden cooling recorded over the Victoria Land Coast region since 0.7 ka might potentially explain our observation of persistent summer fast ice in the Western Ross Sea. Our study has shown that multi-proxy data derived from laminated sediments can provide hitherto unknown detail regarding past summer sea ice dynamics in coastal Antarctic regions. Highlights: Dark and light sediment laminae exhibit different chemical and ecological features. Dark and light sediment laminae reflect different fast ice coverage during summer. Enriched δ 13 C and high IPSO25 (dark laminae) track early thawing of fast ice. High concentration of C. pennatum (light laminae) identifies protracted ice-free conditions. Summer ice-free conditions became less frequent since 0.7 ka BP along the north-western Ross Sea.